Case report: Misdiagnosis of primary mucinous cystadenoma of the testicle by ultrasound - Zhang, Linlin; Xuan, Jianyuan; Li, Manxi; Zhang, Mei; Song, Yu; Pan, Ziang; Fan, Bo; Lu, Lin; Zhou, Hongyan; Li, Yang (Frontiers in Oncology, 2023)
Testicular mucinous cystadenoma is a rare benign testicular tumor with the characteristics of being potentially malignant and showing atypical clinical symptoms; this article reports a case of a primary testicular mucinous cystadenoma misdiagnosed as testicular teratoma by ultrasound. A 69-year-old man was admitted to the hospital because of a 1-year history of left-sided testicular enlargement with scrotal swelling and no obvious abnormalities on laboratory tests. Ultrasound examination revealed solid-mass lesions in the left testicle, suggesting a high probability of teratoma, and contrastenhanced magnetic resonance imaging (MRI) examination suggested an increased possibility of epidermoid cysts. Contrast-enhanced computed tomography (CT) and contrast-enhanced MRI of the preoperative abdomen and pelvis showed no other primary adenocarcinoma. Doctors performed radical resection of the left testicle. The postoperative pathological diagnosis was mucinous cystadenoma, and calcification as well as partially mildly atypical epithelial cells were discovered.2 This is a provisional file, not the final typeset article Furthermore, there were no neoplastic lesions in the epididymis or spermatic cord. No metastatic lesions were found after 6 months postoperative follow-up, and the patient's prognosis remains good.